Descriptive Study of Teacher Professionalism in Learning Process at Mts Negeri Bakalan Rayung of Jombang - Nur Fatimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Keywords: Descriptive Study, Learning Process, Teacher Professionalism Professional teachers are the determinants of education process quality. In order to become professional teachers, they must be able to find to identity and actualize themselves in accordance with the abilities and rules of professional teachers. This research will find the answer of the formula: first, describe what factors can support the professionalism of teachers at MTs Negeri Bakalan Rayung of Jombang; second, describe how the professionalism of teachers in the learning process at MTs Negeri Bakalan Rayung of Jombang, third, describe how the principal's efforts in improving teachers professionalism in the learning process at MTs Negeri Bakalan Rayung Jombang.This type of research was qualitative, and the method of data collection was by using observation, documentation and interview, while the analysis data were inductive, deductive and comparative.The results of this study could be concluded: firstly, the ability of teachers professionalism at MTs Negeri Bakalan Rayung, Jombang was the ability in mastering materials / learning materials, managing teaching and learning programs, managing classes, using media, mastering the foundation of education, managing the interaction of teaching and learning, , recognizing the function of guidance and counseling, know and organize the school administration very well; secondly, the ability of teachers in preparing for teaching is also in very good category. It was indicated that the teacher had prepared the teaching preparation with the correct procedure, each sub chapter of discussion, the teacher had been able to use the instructional media in accordance with its function in delivering the material, and conduct evaluation in every learning process well; thirdly, the effort to improve the teachers professionalism in madrasah is done by the principal and teacher concern. Efforts that had been made by the principal, among others, by holding meetings, upgrading class teachers, and establishing the discipline enforcement on teachers and employees, holding regular meetings among teachers in the field of study and conduct self-assessment.